Highly efficient CO2 capture with simultaneous iron and CaO recycling for the iron and steel industry - Tian, Sicong; Jiang, Jianguo; Yan, Feng; Li, Kaimin; Chen, Xuejing; Manovic, Vasilije (Royal Society of Chemistry, 2016)
An efficient CO2 capture process has been developed by integrating calcium looping (CaL) and waste recycling technologies into iron and steel production. A key advantage of such a process is that CO2 capture is accompanied by simultaneous iron and CaO recycling from waste steel slag. High-purity CaO-based CO2 sorbents, with CaO content as high as 90 wt%, were prepared easily via acid extraction of steel slag using acetic acid. The steel slag-derived CO2 sorbents exhibited better CO2 reactivity and slower (linear) deactivation than commercial CaO during calcium looping cycles. Importantly, the recycling efficiency of iron from steel slag with an acid extraction is improved significantly due to a simultaneous increase in the recovery of iron-rich materials and the iron content of the materials recovered. High-quality iron ore with iron content of 55.1–70.6% has been recovered from waste slag in this study. Although costing nearly six times as much as naturally derived CaO in the purchase of feedstock, the final cost of the steel slag-derived, CaO-based sorbent developed is compensated by the byproducts recovered, i.e., high-purity CaO, high-quality iron ore, and acetone. This could reduce the cost of the steel slag-derived CO2 sorbent to 57.7 € t−1, appreciably lower than that of the naturally derived CaO. The proposed integrated CO2 capture process using steel slag-derived, CaO-based CO2 sorbents developed appears to be cost-effective and promising for CO2 abatement from the iron and steel industry.